The Rasch analysis of mathematics teachers' practices on teaching thinking skills - Zulkpli, Z. (Serials Publications, 2017)
Teaching thinking is the fundamental pillar in determining the success of integrating thinking skills in teaching and learning mathematics, hence teaching thinking skills is an important issue in the education system today. Several studies showed that the teachers are still not ready to teach thinking skills due to insufficient knowledge about thinking skills. The present quantitative study identified the practices of teaching thinking skills among teachers. In this study, 199 mathematics teachers in Johor were selected using stratified sampling technique and the Rash analysis was then analyzed. Results showed that most of the mathematics teachers relatively did more practices on lower order thinking (LOT) compared to higher order thinking (HOT) in teaching thinking skills. This study provided a clear proof in favor of Rasch analysis as an appropriate way for the teachers and studies to obtain moreinterpretations on the level of teachers' practices in teaching thinking skills.